ASSESSMENT OF KNOWLEDGE REGARDING GESTATIONAL DIABETES MELLITUS AMONG PREGNANT WOMEN IN MATERNITY TEACHING HOSPITAL, SULAIMANI CITY - Mahmood, Avin Ali; Khalil, Rozhan Yassin (Journal of Sulaimani Medical College, 2025)
Background Gestational diabetes has risen in recent years. This condition may lead to extremely negative outcomes for both mother and baby. Knowledge is one of the important aspects of enhancing women’s level of education regarding this condition. Objectives The main aim of this study was to assess pregnant women’s knowledge regarding gestational diabetes mellitus. Materials and Methods Quantitative descriptive design (non-probability sample). The method was used to rectitude 140 pregnant women diagnosed with gestational diabetes mellitus and attending the Center of Diabetes at Maternity Teaching Hospital in Sulaimani. Results In this study, 140 pregnant women were enrolled with an age range between 21 and 40 years old, with a mean of 32.2 ± 5.7 years, and less than half were between ages 35-40 years. Overall, more than half of the pregnant women (59.3%) had fair knowledge regarding gestational diabetes mellitus, whereas only 4.3 % had good knowledge. Conclusions The fi ndings revealed a lack of knowledge in pregnant women regarding gestational diabetes mellitus. Nurses must play an important role in health education about gestational diabetes mellitus in pregnant women and minimise the risk of complications.
Keywords: Assessment; Pregnant women; Knowledge; Gestational Diabetes Mellitus; Sulaimani MaternityTeaching Hospital